Linguistic poetry and anthropomorphism. Around Zbigniew Bieńkowski’s poetic historiosophy - Agata Stankowska (Przestrzenie Teorii)
The sketch presents the reconstruction of Zbigniew Bieńkowski’s theory of linguistic poetry. This author who is classified by critics and researchers as a member of linguistic poetry movement is by no means uncritical of its various perspectives and accomplishments. This complicated approach is reflected in the dispute that Bieńkowski was engaged in with Karpowicz and the poets of the New Wave in his critical sketches. He unfairly accuses them of being too minimalistic and of paying too much attention to linguistic experiments. He claims that distrust of language and its communicative functions in New Wavers’ programs overshadowed the broad philosophical and ideological functions of word games. Instead he proposed his own poetological project “Trzy poematy” [“Three poems”], where avant-garde traditions mingled with symbolist ones and called for breaking the numbness of language for broader, idealistic purposes. Referring to Vico’s historiosophy, Bieńkowski wishes to treat linguistic poetry both as a tool (a trick) and space for intervention, whose final purpose is to rebuild the anthropogenic locus amoenus in language.